CERTAINTY AS A CONDITION OF POSSIBILITY FOR ALL CONDITIONS OF POSSIBILITY - Jaued, Lucas (Revista Gênero e Interdisciplinaridade, 2026)
This article argues that intrinsic phenomenological certainty constitutes the ultimate condition of possibility for all phenomenality, including the very structure of the internal consciousness of time described by Husserl (2012, 2019). It argues that temporal experience—characterized by retention, impression, and protension—cannot be founded simply on a flow devoid of prior identity, symmetry, and stability. Rather, the very possibility of flow, succession, and duration presupposes absolute formal singularities, understood here as expressions of original certainty. Based on the theory of the informational singularity of self-consciousness (ISA), it proposes a phenomenology of certainty that is more fundamental and more general than the Husserlian phenomenology of time, capable of explaining not only how experience is articulated temporally, but also why something can appear as experience in the first place. The article argues, therefore, that every condition of relative possibility (temporal, relational, negative) depends on conditions of absolute possibility (intrinsic, affirmative, non-contrastive), reformulating classical notions of identity, intentionality, self-awareness, and their phenomenological foundations.